Social Acceptability and Health Concerns of Smoking and Vaping Among University Students: A Cross-Sectional Study - Afsheen Maqsood; Wan Nazatul Shima Shahidan; Daud Mirza; Naseer Ahmed; Artak Heboyan (Tobacco Use Insights)
Objective This study aimed to assess tobacco and vaping habits among university students, exploring awareness of university policies, attitudes, and behaviors related to smoking and vaping. Methods An online questionnaire was distributed among students from various universities, including institutions in Pakistan, covering demographics, smoking and vaping behaviors, awareness of policies, and beliefs. Data was analyzed using descriptive statistics, Binomial tests, Chi-square tests, and logistic regression. Results Out of the total 683 respondents, 65.02% were female, and 34.98% were male. Most participants were undergraduate students (71.31%), with Dentistry being the most represented field (50.36%). Most students perceived smoking or vaping as socially acceptable (58.3%) and were aware of university policies (59.3%). However, 46.6% were aware of cessation programs. Most of the students expressed concern about long-term vaping health risks (74.5%). Logistic regression identified gender (Male) and field of study (Dentistry) as significant predictors of policy awareness. Conclusion University students exhibit varied perceptions and behaviors related to smoking and vaping. The study highlights the importance of implementing effective policies and interventions to address tobacco and vaping use among them.